Thermal cabin model development for interior climate simulations: A co-simulation approach using GT-SUITE and TAITHERM - Gnanasundaram, Karthikeyan; Muralidharan, Harikrishnan (My University, 2023)
With the increased focus on electric vehicles, decreasing the energy consumption of the climate system is becoming increasingly important. In order to achieve that, a thermal model of the car cabin that can predict the temperature at different zones in the cabin accurately is highly desired. The model should be able to predict the cabin temperature for different ambient conditions as well as different HVAC conditions. The thesis focuses on developing such a model and analysing the results by comparing them with experimental data. A co-simulation methodology developed by Gamma Technology was used where the fluid domain in the cabin was solved by GTSuite and the temperature of the cabin wall structures was solved by TAITherm. These models exchange data at prescribed communication intervals so that the thermal features in the cabin can be captured accurately. The model needed to be calibrated against experimental data by using a Heat Transfer Coefficient Multiplier (HTCM). To increase the accuracy of the solution and to eliminate the need for calibration, an extension of this method where CFD data from steady-state simulations carried out in Star CCM+ were mapped onto the co-simulation model. The results from both methods were compared with the experimental data and have been discussed in detail in this thesis.
Keywords: cabin model; co-simulation; CFD; climate system; HVAC; heat transfer; GT-Suite; TAITherm; Star CCM+